The Modern Economic, Technological, and Societal Trends: New Challenges or Opportunities. Conference Proceedings, November 27-29, 2024 - Subačienė, Rasa; Tamulevičienė, Daiva (Vilnius University Proceedings, 2024)
The conference proceedings include abstracts from presentations at the Fifth International Scientific Conference on Accounting, Audit, and Analysis, titled “The Modern Economic, Technological, and Societal Trends: New Challenges or Opportunities”. This conference is dedicated to evaluating the evolution and modernization of accounting, auditing, and financial analysis, covering trends in accounting theory, practice, and regulation; technological transformations; shifts in audit methodologies; advancements in financial and business management practices; and the role of governance and accountability in addressing sustainability and climate-related challenges.
Keywords: -